Materials for Springs - Yamada, Yoshiro; Kuwabara, Toshio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
(3z(BMaterials for springs(3y (Bis basically intended for engineers related to spring materials and technologies who graduated from metallurgical or mechanical engineering courses in technical high school, or in other higher engineering schools, as well as those who are related to the purchase or sales of spring materials. The first chapter introduces into the fundamental selection processes of spring materials including the information sources on materials database. It is followed by the basic mechanisms and theories of spring failures such as fatigue fracture, creep/stress relaxation and stress corrosion cracking of metallic materials. The focuses of the second chapter is put on ferrous and non-ferrous metallic materials, including some materials developed in these two decades, such as high strength automobile suspension steels etc. In the third and fourth chapters, polymer materials, FRP (Fiber Reinforced Plastics), ceramics and C/C composite materials are the main subject respectively. In the fifth chapter, lists of Japanese spring material manufacturers and their material grades being produced, comparisons of spring materials in the Japanese Industrial Standards with some other foreign standards, etc, are summarized.s
A Guide to Spring Material Selection -- Metallic Material for Springs -- Polymeric Materials -- Inorganic Materials.
Keywords: Engineering; Mechanical engineering; Machinery; Materials science; Engineering; Mechanical Engineering; Materials Science, general; Machinery and Machine Elements; Electronic books